(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nashik District is located between 180 33’’ and 200 .53’’ North latitude and between 730 .16’’ degree and 750 .16’’ East Longitude at Northwest part of the Maharashtra state, at 565 meters above mean sea level. The District has great mythological background. The Godavari river originates from Trimbakeshwar in Nashik. One of the 12 Jyotirlingas also at Trimbakeshwar. Nashik has given many well-known historical and literature personalities like Veer Sawarkar, AnantKanhere, Rev. Tilak, Dadasaheb Potnis, Babubhai Rathi, V.V. Shirwadkar and VasantKanetkar, Kusumagraj. Nashik is also known as Mini Maharashtra, because the climate and soil conditions of Surgana, Peth, Igatpuri resembles with Konkan. Niphad, Sinnar, Dindori, Baglan blocks are like Western Maharashtra and yeola, Nandgaon, Chandwad blocks are like Vidarbha Region. Nashik, Malegaon, Manmad, Igatpuri are some of the big cities situated in the Nashik District. Nashik district is the third largest district in Maharashtra in terms of Population of 61,09,052 and area occupying an area of 15,582 square kilometres in the north Maharashrta region. It is bounded by Dhule district to the north, Jalgaon district to the east, Aurangabad district to the southeast, Ahmednagar district to the south, Thane district to the southwest, Valsad and Navsari districts of Gujarat to the west, and The Dangs district to the northwest. The Western Ghats or Sahyadri range stretches from north to south across the western portion of the district. Nashik is the third largest city of Maharashtra after Mumbai & Pune. Nashik lies in the northern part of Maharashtra state at 700 m (2,300 ft) from the mean sea level which gives it ideal temperature variation, particularly in winters. Nashik lies at altitude of 700m above sea level and has lush mountainous terrain. The river Godavari originates from the Brahmagiri Mountain, Trimbakeshwar about 24 km (15 mi) from Nashik and flows through the old residential settlement, now in the central part of the city. Other than Godavari, important rivers like Vaitarana, Bhima, Girana, Kashyapi and Darana flow across Nashik. The city has a historical background also. Nashik district and city is also well-known for its agricultural development. Crops like grapes and onion are exported from the district all over the world in large quantity.